COVID-Related Thrombosis and Overall Implications Related to Percutaneous Interventions - Lookstein, Robert A. (Seminars in Interventional Radiology, 2022)
The SARS-COV-2/ COVID-19 pandemic created unique, once in a lifetime challenges for healthcare workers across the globe. One of the challenges specific to interventional radiology was the increased incidence of vascular thrombosis leading to urgent and emergent clinical patient management issues. Limited healthcare resources and complex clinical presentations required innovative solutions, and workflows to manage the increased burden on the healthcare providers.
Keywords: thrombosis; COVID-19; peripheral vascular disease